2017
DOI: 10.2147/por.s132839
|View full text |Cite
|
Sign up to set email alerts
|

Real-life effectiveness and safety of the inhalation suspension budesonide comparator vs the originator product for the treatment of patients with asthma: a historical cohort study using a US health claims database

Abstract: Objective: The objective of this study was to determine whether the effectiveness of budesonide comparator is non-inferior to budesonide reference in the prevention of asthma exacerbations. Asthma-related hospitalizations and safety were also examined. Methods: This study used a matched, historic cohort design. Data were drawn from the Clinformatics ™ Data Mart US claims database and included a 1-year baseline, starting 1 year before the index prescription date, and a 1-year outcome period. Patients received b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 30 publications
(41 reference statements)
1
12
0
3
Order By: Relevance
“…Consistent with previous studies investigating the use of BIS nebulization in asthmatics,424344 the current study also showed no effect of treatment on hypothalamic-pituitary-adrenal (HPA) axis suppression as evidenced by lack of significant changes in morning serum cortisol over the treatment period. Serum cortisol levels of the treated patients did not differ from the reference values of the laboratory; however, serum cortisol was reduced by 18.7% in the BIS-treated group, 2.2% in the nasal spray-treated group and 87.9% in the oral methylprednisolone-treated group.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies investigating the use of BIS nebulization in asthmatics,424344 the current study also showed no effect of treatment on hypothalamic-pituitary-adrenal (HPA) axis suppression as evidenced by lack of significant changes in morning serum cortisol over the treatment period. Serum cortisol levels of the treated patients did not differ from the reference values of the laboratory; however, serum cortisol was reduced by 18.7% in the BIS-treated group, 2.2% in the nasal spray-treated group and 87.9% in the oral methylprednisolone-treated group.…”
Section: Discussionsupporting
confidence: 91%
“…The remaining were a prospective cohort study 36 and a genome-wide association study. 37 All studies utilized EHR data, of which 18 (69.2%) [14][15][16]18,19,22,23,[25][26][27][28][29][30][31][32][34][35][36] analyzed claims databases as well. The sample sizes ranged from 100 to 1000 (n = 4, 15.4%), 1001 to 10 000 (n = 7, 26.9%), and > 10 000 (n = 15, 57.7%).…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Будесонид суспензия отличается высоким профилем безопасности, что доказано многочисленными исследованиями [18][19][20][21]. Длительная терапия будесонид суспензией детей с БА не оказывала влияния на их конечный рост [19].…”
Section: терапия бронхиальной обструкции на фоне вирусной инфекцииunclassified
“…Кроме того, не было значимой разницы в минеральной плотности и уровне кальция в костях между получавшими будесонид и детьми контрольной группой [20]. Благодаря этим данным препарат разрешен детям раннего возраста, начиная с 6 месяцев, беременным женщинам и кормящим матерям [18].…”
Section: терапия бронхиальной обструкции на фоне вирусной инфекцииunclassified
See 1 more Smart Citation